Astrology as a Social Framework: The ‘Children of Planets’, 1400–1600 - Shamos, Geoffrey (Journal for the Study of Religion, Nature and Culture, 2014)
During the Early Modern period, many believed that the seven planets—Mercury, Venus, Mars, Jupiter, Saturn, the sun, and the moon—affected the course of terrestrial events and determined the temperament, complexion, profession, and even the manner of death of individuals. Such concepts were depicted by artists in a series of images commonly referred to as the ‘Children of the Planets’. By merging scientific knowledge and popular imagery, the convention helped to shape the contemporary understanding of the cosmos. Astrology is often described in terms of the correspondence between the macrocosm and the microcosm or the universe and the individual, but by linking diverse individuals according to mutual planetary affiliations, the ‘Children of the Planets’ also offered a system for categorizing corporate identity and defining social relations.